2003
DOI: 10.1038/sj.hdy.6800262
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of sexual reproduction in Romanian populations of the aphid Sitobion avenae inferred from phenotypic and genetic structure

Abstract: Models of coexistence of sexual and asexual lineages in aphids assume that obligate parthenogenetic lineages predominate in areas with mild winter climate because of their high reproductive output, while sexual lineages predominate in areas with severe winter because they produce eggs resistant to frost. To validate this hypothesis in natural conditions, the reproductive mode of populations of the aphid Sitobion avenae was assessed in two very contrasting climatic situations, Romania (severe winter) and Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
6
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 37 publications
7
81
6
1
Order By: Relevance
“…Chilean populations of S. avenae encompass a few heterozygous multilocus genotypes In contrast to reports for European populations Simon et al, 1999a;Haack et al, 2000;Llewellyn et al, 2003Llewellyn et al, , 2004Papura et al, 2003), S. avenae populations in Chile showed a very low clonal diversity, independent of the host plant, geographic zone, or sampling season. As compared with the 4% of genotypic Figure 2 Neighbour-joining tree based on Goldstein's distance (Goldstein et al, 1995) calculated with five microsatellite loci for the 44 multilocus genotypes discriminated in Chilean populations of Sitobion avenae.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Chilean populations of S. avenae encompass a few heterozygous multilocus genotypes In contrast to reports for European populations Simon et al, 1999a;Haack et al, 2000;Llewellyn et al, 2003Llewellyn et al, , 2004Papura et al, 2003), S. avenae populations in Chile showed a very low clonal diversity, independent of the host plant, geographic zone, or sampling season. As compared with the 4% of genotypic Figure 2 Neighbour-joining tree based on Goldstein's distance (Goldstein et al, 1995) calculated with five microsatellite loci for the 44 multilocus genotypes discriminated in Chilean populations of Sitobion avenae.…”
Section: Discussionmentioning
confidence: 46%
“…Firstly, the genotypes that became established may have been continuously parthenogenetic since their introduction because of the mild climate prevalent in areas where cereal crops are cultivated in Chile. After many rounds of parthenogenetic generations, S. avenae populations in Chile could have accumulated high levels of heterozygosity through allelic divergence at neutral nuclear loci, as previously proposed for other asexual lineages of aphids (for Rhopalosiphum padi see Simon et al, 1999b;Delmotte et al, 2001Delmotte et al, , 2002 for Myzus persicae see Vorburger et al, 2003; for S. avenae and other related species see Wilson et al, 1999Wilson et al, , 2003Papura et al, 2003). Alternatively, it has been found recently that asexual lineages of aphids can arise from hybridization: either between two distinct parental species or between differentiated lineages of the same species (Delmotte et al, 2002Simon et al, 2003).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous genetic studies on aphids have reported deviation from Hardy-Weinberg Equilibrium because of heterozygosity excess (Papura et al, 2003;Vialatte et al, 2005). Michel et al (2009a) observed similar levels of heterozygote excess with the soybean aphid, with more deviation present in early collected populations.…”
Section: Heterozygosity Excessmentioning
confidence: 81%
“…In the past ten years, increasing studies have revealed genetic structural differences between sexual and asexual lineages using microsatellites. In general, genotypic diversity was higher in sexual than in asexual lineages (Delmotte et al, 2002;Papura et al, 2003). In addition, heterozygosity excess, linkage disequilibrium and deviation from Hardy-Weiberg equilibrium occurred Seasonal genetic structure in Beijing populations of the grain aphid Sitobion miscanthi (Takahashi): an investigation using microsatellites more often in asexual lineages (Normark, 1999;Simon et al, 1999;Guillemaud et al, 2003;Vorburger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%